Evidence‐based Danish guidelines for screening of diabetic retinopathy. Issue 8 (11th October 2018) - Grauslund, Jakob; Andersen, Nis; Andresen, Jens; Flesner, Per; Haamann, Per; Heegaard, Steffen; Larsen, Michael; Laugesen, Caroline Schmidt; Schielke, Katja; Skov, Jesper; Bek, Toke
Abstract: Purpose: Diabetic retinopathy (DR) is among the leading causes of visual loss in the working‐age population. It is generally accepted that screening of DR is cost‐effective and can detect DR before it becomes sight‐threatening to allow timely treatment. Methods: A group of retinal specialists was formed by the Danish Ophthalmological Society with the aim to formulate contemporary evidence‐based guidelines for screening of DR in order to implement these in the Danish screening system. Results: We hereby present evidence for DR‐screening regarding (1) classification of DR, (2) examination techniques, (3) screening intervals and (4) automated screening. It is our recommendation that the International Clinical Retinopathy Disease Severity Scale should be used to classify DR. As a minimum, mydriatic two‐field disc‐ and macular‐centred images are required. In the case of suspected clinically significant diabetic macular oedema, supplementary optical coherence tomography can increase the diagnostic accuracy. There is solid evidence to support a flexible, individualized screening regimen. In particular, it is possible to prolong screening intervals to 24–48 months for patients with no or mild nonproliferative diabetic retinopathy (NPDR), but it is also possible to use extended intervals of 12–24 months for patients with moderate NPDR given that these are well‐regulated regarding glycaemic control (HbA1c ≤ 53 mmol/mol) and blood pressure (≤130/80 mmHg). Automated screening of DR is encouraging but is not ready for implementation at present. Conclusion: Danish evidenced‐based guidelines for screening of DR support high‐quality imaging and allow flexible, individualized screening intervals with a potential for extension to patients with low risk of DR progression.